Progress in Electrocatalytic Hydrogen Evolution Based on Monolayer Molybdenum Disulfide - Wang, Chuan; Huang, Jinzhao; Chen, Jiayue; Xi, Zhongxin; Deng, Xiaolong (Frontiers in Chemistry, 2019)
Energy and environmental issues raise higher demands on the development of a sustainable energy system, and the electrocatalytic hydrogen evolution is one of the most important ways to realize this goal. Two-dimensional (2D) materials represented by MoS2 have been widely investigated as an efficient electrocatalyst for the hydrogen evolution. However, there are still some shortcomings to restrict the efficiency of MoS2 electrocatalyst, such as the limited numbers of active sites, lower intrinsic catalytic activity and poor interlayer conductivity. In this review, the application of monolayer MoS2 and its composites with 0D, 1D and 2D nanomaterials in the electrocatalytic hydrogen evolution were discussed. On the basis of optimizing the composition and structure, the numbers of active sites, intrinsic catalytic activity and interlayer conductivity could be significantly enhanced. In the future, the study would focus on the structure, active site and interface characteristics, as well as the structure-activity relationship and synergetic effect. Then, the enhanced electrocatalytic activity of monolayer MoS2 can be achieved at the macro, nano and atomic levels, respectively. This review provides a new idea for the structural design of two-dimensional electrocatalytic materials. Meanwhile, it is of great significance to promote the study of the structure-activity relationship and mechanism in catalytic reactions.